2021
DOI: 10.3390/f12091252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Capability of Unmanned Aerial System (UAS) Imagery to Detect and Measure the Effects of Edge Influence on Forest Canopy Cover in New England

Abstract: Characterizing and measuring the extent of change at forest edges is important for making management decisions, especially in the face of climate change, but is difficult due to the large number of factors that can modify the response. Unmanned aerial systems (UAS) imagery may serve as a tool to detect and measure the forest response at the edge quickly and repeatedly, thus allowing a larger amount of area to be covered with less work. This study is a preliminary attempt to utilize UAS imagery to detect change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 109 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…For CHMC, the coarse resolution of DEM, which is very common in traditional vegetation surveys, may be the primary reason for the poor performance, but the influence of noise is greatly weakened by HSTAC based on the same DEM (Erikson & Olofsson, 2005;Nyamgeroh et al, 2018;Wang et al, 2004). Moreover, as the point cloud in CHMC was missing in small to moderate-sized gaps in our study, it is unable to accurately identify these gaps, affecting long-term monitoring of species composition and forest succession dynamics (Grybas & Congalton, 2021;White et al, 2018). In terms of spatial matches and mismatches between canopy gaps, our study demonstrated that the HSTAC method estimated the number of gaps more accurately than PBSC and OBIA.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…For CHMC, the coarse resolution of DEM, which is very common in traditional vegetation surveys, may be the primary reason for the poor performance, but the influence of noise is greatly weakened by HSTAC based on the same DEM (Erikson & Olofsson, 2005;Nyamgeroh et al, 2018;Wang et al, 2004). Moreover, as the point cloud in CHMC was missing in small to moderate-sized gaps in our study, it is unable to accurately identify these gaps, affecting long-term monitoring of species composition and forest succession dynamics (Grybas & Congalton, 2021;White et al, 2018). In terms of spatial matches and mismatches between canopy gaps, our study demonstrated that the HSTAC method estimated the number of gaps more accurately than PBSC and OBIA.…”
Section: Discussionmentioning
confidence: 80%
“…Using high‐resolution RGB images, HSTAC was applied to detect forest canopy gaps, and three other common methods (PBSC, OBIA, CHMC) were only used as a comparison to HSTAC. Before classification, we matched and compensated the hue ( H ), intensity ( I ), and saturation ( S ) values of the shadow areas in the HIS spaces based on the optical characteristics of forest shadows to eliminate the shadow to a certain extent (Grybas & Congalton, 2021). Meanwhile, the visible‐band difference vegetation index (VDVI) was computed from the RGB bands to further reduce shadow effects across the scene (De Petris et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations